Investigation of Mechanical Properties of Shale Rock in Qassim Region, Saudi Arabia - Irfan M. Α.; Almufadi, F. A. (Engineering, Technology & Applied Science Research, 2019)
An investigation into the mechanical properties of shale rock from Qassim Province, Saudi Arabia is presented in this paper. Uniaxial compression test, Schmidt hammer test and porosity estimation were carried out. Regarding the compression test, it was found that the strength ranged from 1.98MPa to 8MPa and the strain ranged from 0.53% to 2.5%. Regarding the Schmidt Hammer test, it was found that the rebound values ranged from 22.4 to 25. The measurements of volumetric porosity indicated that the porosity in the shale rock ranged between 19.12% and 24.31%. All the values determined in this project match well with the published values of other studies about shale rock.